Worker Protection Standard: Application Exclusion Zone (AEZ) - Frederick M. Fishel; Tatiana Sanchez (EDIS, 2016)
The Worker Protection Standard (WPS) is a Federal regulation designed to protect agricultural workers (people involved in the production of agricultural plants) and pesticide handlers (people mixing, loading, or applying pesticides or doing other tasks involving direct contact with pesticides). The “Application Exclusion Zone” or AEZ is a new term used in the WPS rule; it refers to the area surrounding the pesticide application equipment. This 3-page fact sheet explains this new rule. Written by Frederick M. Fishel and Tatiana Sanchez, and published by the Agronomy Department, August 2016.